Coverage and Knowledge Regarding Human Papillomavirus Vaccination Among Female Medical Students at Pelita Harapan University - Lukman, Leni (Fakultas Kedokteran Universitas Pelita Harapan, 2025)
Background: Cervical cancer is the fourth most common cancer among women worldwide. Human papillomavirus (HPV) is the primary cause of cervical cancer. One of the key preventive measures to reduce the incidence of cervical cancer is immunization. According to the data from the World Health Organization year 2020, the national HPV vaccination coverage in Indonesia was only 5% for the complete dose and 6% for the first dose. Lack of knowledge is one of the contributing factor of HPV vaccination coverage. Methods: This study was conducted with cross-sectional design. This study used primary data which was collected using questionnaires. The questionnaire has been tested for validity and reliability in previous study. The subjects were female students of Faculty of Medicine University of Pelita Harapan. Results: Our of 770 subjects with mean age of 20.3 years old, 490 subjects (63.6%) never got HPV vaccination, 102 subjects (13.3%) were not fully vaccinated and 178 subjects (23.1%) were fully vaccinated. Age at first dose of HPV vaccination was 9-14 years old in 123 subjects (43.9%) and > 15 years old in 157 subjects (56.1%). From all of the HPV vaccinated subjects, 18 subjects (6.4%) got bivalent vaccine, 52 subjects (18.6%) got quadrivalent vaccine and 64 subjects (22.9%) got nonvalent vaccine. Majority of the subjects (354 subjects, 46%) had good knowledge regarding HPV vaccination, 271 subjects (35.2%) had sufficient knowledge and 145 subjects (18.8%) had poor knowledge. Conclusions: Despite sufficient knowledge regarding HPV vaccination among majority of female medical students at Pelita Harapan University, HPV vaccination coverage remained suboptimal.